Hardware Implementation of Digital Base Band Videophone - 秦仁忠; 孟焱; 张家谋 (Tongxin xuebao)
The design and realization of 64kb/s digital monochrome videophone,which has been implemented in hardware,is discussed in this paper.The structure graph of hardware system,as well as flowsheet of control software in codec is showed. Some suggestions,including the improvement of image quality and the increasement of frame frequency,are also presented.